Undifferentiated endometrial carcinoma diagnosed during perimenopausal hormone therapy: a case report and literature review - Wang, Ying; Zheng, Yu-Tong; Zhang, Ling; Cao, Xue-Quan; Lin, Zhu; Liu, Hong-Yu; Hu, Qiong-Ying (Frontiers in Oncology, 2024)
Uterine corpus endometrial carcinoma, one of the three most frequent cancers of the female reproductive system, primarily affects women who are perimenopausal or postmenopausal. Moreover, it is an epithelial cancer that develops in the endometrium, which is classified as either estrogen-dependent (type I) or non-estrogen-dependent (type II). Non-estrogen-dependent endometrial cancers include plasma cell carcinoma and undifferentiated/dedifferentiated endometrial carcinoma. Undifferentiated endometrial carcinoma is a rare but aggressive endometrial epithelial cancer that lacks any histologic differentiation and is classified as a high-grade endometrial cancer. This case presents that a patient had uterine corpus endometrial carcinoma during perimenopausal hormone therapy, and the patient was treated with sequential estrogen–progestin treatment for 3 years. During that period, she did not undergo a follow-up examination for the last 2 years due to the pandemic. Undifferentiated endometrial carcinoma is a special type of endometrial cancer that is not hormone-dependent, and whether the occurrence of this case is related to perimenopausal hormone therapy needs to be verified by more evidence-based clinical cases and further studies.